HISTORICAL FORMING OF ETIQUETTE WORDS - Nauryzova, A.K. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The article deals with the role of addressing by Name or Family name, and its stylistic usage. Etiquette words characterize interrelation of speakers, which shows the degree of their relationship. Each nation in accordance with its national features and psychology uses variously etiquette words in ad-dressing to someone, sometimes with name, middle name and family names in a different way. The given work describes the usage of etiquette words in communication of Karakalpak people. To be considered a member of certain social groups, a certain nationality, the people, tribal and other state, economic, political or cultural organizations (men, women, the elderly, youth, children, rural and urban residents) make them act according to the respective plans and procedures, obey them, follow schematic stereotypes that are inherent only to them. Similarly, the totality of the culture of action ripened, formed in the relations between people and who have fallen into a definite system, have recently been called the term etiquette. Etiquette is a philosophical, ethical and, on the other hand, pedagogical concept; Ie, they are con-sidered as a set of actions, ordered and systematized among people. After gaining independence and three or four years before it paid great attention to the national languages, national and nationwide rites and traditions, values, after their revival in Uzbekistan and the sovereign Karakalpakstan a new spiritual atmo-sphere was formed, we became even more clearly aware of our identity. Along with the national spiritual and material wealth, special attention is paid to the culture of language, especially its purity. In our opinion, all of this, indeed, is a spiritual unit that has an integral synthesis of speech etiquette, which is firmly linked to all of the above stated. Proceeding from such points of view, taking into account the spiritual requirements of our people and nations, growing at the present stage with each passing day, we believe that the special study of ques-tions of speech etiquette in modern Karakalpak language, its features, to bring in a certain scientific system one of the actual tasks of today's national linguistics. That’s because, any language of nation or nationality definitely has its own specificity of speech etiquette, which is a natural phenomenon. The words of etiquette in modern Karakalpak language constitute the object of research. But the identification of the role of using units of speech etiquette in forming the norms of the literary language, their consideration as the main features of the cultural speech, comparative study of the features of the speech etiquette with the Turkic languages in accordance with the internal laws of the language are con-sidered the subject of the study. Comparative analysis of materials related to speech etiquette is one of the methods of study of the philosophical, everyday, ethical and pedagogical views of the study in the linguistic aspect. We realized this, studying and taking into account the works of representatives of Russian, Uzbek, Kazakh linguistics, who had previously studied this issue with the scientific-theoretical, material points of view. When writing the work, historical, comparative-historical, descriptive methods were applied.